A diffuse large B‐cell thyroid lymphoma presented as a compressive goiter in a young woman with no evidence of Hashimoto's thyroiditis. Issue 7 (9th July 2021) - Oueslati, Ibtissem; Chatti, Hiba‐Allah; Yazidi, Meriem; Chaker, Fatma; Chihaoui, Melika
Abstract: Thyroid lymphoma should be suspected in case of rapid enlargement of the thyroid gland even in a young patient with no history of Hashimoto thyroiditis. The confirmation is based on histopathology and immunohistochemistry. Abstract : Thyroid lymphoma should be suspected in case of rapid enlargement of the thyroid gland even in a young patient with no history of Hashimoto thyroiditis. The confirmation is based on histopathology and immunohistochemistry.